Evaluating good husbandry practices and organic fermented additives for coccidiosis control in a pilot study using slow-growing broilers - Rodriguez, Anabel Elisa; Britez, Jesica Daiana; Pisón-Martínez, María Luz; Delgado, Fernando Oscar; Balbiani, Facundo; Berardo, Cecilia Carolina; Gramaglia, Cesar Ivan; Cuba, Facundo; Poklepovich Caride, Tomás Javier; Moreno, Claudia Elvira; Francinelli, Gladys Beatriz; Morici, Gabriel Edgardo; et al. (MDPI, 2025)
The Argentine Campero-INTA slow-growing chicken, a widely used breed in family poultry farming, faces high coccidiosis prevalence, impairing productivity. Control often relies on management and drugs due to vaccination costs. This pilot study assessed the breed’s susceptibility to local Eimeria and the impact of good animal welfare practices (AWPs) and an organic fermented additive, locally produced, combined with AWPs (OF-AWPs). Two trials evaluated productive (body weight gain and feed conversion), infection (oocyst excretion and lesion score), and histopathological parameters (villus height and crypt depth). The productivity (PI) and anticoccidial (ACI) indexes were calculated. Metagenomic analysis of the additive was also conducted. Mild to moderate coccidiosis significantly reduced PI (7.99–16.83 vs. 29.29 in unchallenged controls). In the second trial, AWPs showed good anticoccidial efficacy (ACI 173.9), while OF-AWPs demonstrated high efficacy, especially in birds of 28 days (ACI 180.6), improving productive parameters, reducing oocyst shedding, and enhancing the villus height to crypt depth ratio. Over a 75-day cycle, the OF-AWP increased the PI by 24.44% compared to untreated chickens (108.8 vs. 87.43). Lactic acid bacteria were the main component of the organic fermented additive. This research highlights the potential of an agroecological strategy to manage coccidiosis in Campero-INTA chickens.